A digital self-care intervention for Ugandan patients with heart failure and their clinicians: User-centred design and usability study - Jason Hearn; Sahr Wali; Patience Birungi; Joseph A Cafazzo; Isaac Ssinabulya; Ann R Akiteng; Heather J Ross; Emily Seto; Jeremy I Schwartz (Digital Health, 2022)
Background The prevalence of heart failure (HF) is increasing in Uganda. Ugandan patients with HF report receiving limited information about their illness and associated self-care behaviours. Interventions targeted at improving HF self-care have been shown to improve patient quality of life and reduce hospitalizations in high-income countries. However, such interventions remain underutilized in resource-limited settings like Uganda. This study aimed to develop a digital health intervention that enables improved self-care amongst HF patients in Uganda. Methods We implemented a user-centred design (UCD) process to develop a self-care intervention entitled Medly Uganda . The ideation phase comprised a scoping review and preliminary data collection amongst HF patients and clinicians in Uganda. An iterative design process was then used to advance an initial prototype into a functional digital health intervention. The evaluation phase involved usability testing of the intervention amongst Ugandan patients with HF and their clinicians. Results Medly Uganda is a digital health intervention that allows patients to report daily HF symptoms, receive tailored treatment advice and connect with a clinician when showing signs of decompensation. The system harnesses Unstructured Supplementary Service Data (USSD) technology that is already widely used in Uganda for mobile phone-based financial transactions. Usability testing showed Medly Uganda to be both acceptable and feasible amongst clinicians, patients and caregivers. Conclusions Medly Uganda is a functional digital health intervention with demonstrated acceptability and feasibility in enabling Ugandan HF patients to better care for themselves. We are hopeful that the system will improve self-care efficacy amongst HF patients in Uganda.